Analisis Alternatif Percepatan Projek Reparasi ORCA LAUT 7296 Mengguankan Metode Korelasi SPSS - Anauta Lungiding A.R; Nely Handayani Kusuma Hadi (Jurnal Publikasi Ilmu Manajemen, 2023)
Repair activities are one of the ship maintenance schedules. In the ORCA LAUT 7296 ship repair project, acceleration of project activities is carried out to save repair time. This is done so that the ship can operate immediately and the shipyard can receive a new ship project that you want to repair or build a new ship. ORCA LAUT 7296 has several jobs, especially on hull replating activities due to the ship having run aground and experiencing a leak. In this study, an analysis of project acceleration was carried out using the correlation method with the help of the SPSS application. Analysis is carried out to obtain the best alternative to accelerate the project. The results of this study can be carried out as much as 30% of project acceleration through the addition of 3 hours of overtime hours so that, from the beginning the target was completed in 34 days after acceleration, it became 25 days.